2019
DOI: 10.1186/s12864-019-6245-5
|View full text |Cite
|
Sign up to set email alerts
|

Maize transposable elements contribute to long non-coding RNAs that are regulatory hubs for abiotic stress response

Abstract: BackgroundSeveral studies have mined short-read RNA sequencing datasets to identify long non-coding RNAs (lncRNAs), and others have focused on the function of individual lncRNAs in abiotic stress response. However, our understanding of the complement, function and origin of lncRNAs – and especially transposon derived lncRNAs (TE-lncRNAs) - in response to abiotic stress is still in its infancy.ResultsWe utilized a dataset of 127 RNA sequencing samples that included total RNA datasets and PacBio fl-cDNA data to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 86 publications
9
39
1
Order By: Relevance
“…The WRKY family transcription factors have been widely studied in various plants under cold stress [72][73][74]. Some TFs in the WRKY family have been reported as hubs in plant co-expression networks under abiotic stress, including cold stress [75]. In this work, a novel putative lncRNA (ncP456) was predicted to directly bind complementarily with Manes.09G112700, annotated as WRKY DNA-binding protein 33 ( Figure S22).…”
Section: Functional Analysis Of Potential Novel Lncrnas Involved In Cmentioning
confidence: 86%
“…The WRKY family transcription factors have been widely studied in various plants under cold stress [72][73][74]. Some TFs in the WRKY family have been reported as hubs in plant co-expression networks under abiotic stress, including cold stress [75]. In this work, a novel putative lncRNA (ncP456) was predicted to directly bind complementarily with Manes.09G112700, annotated as WRKY DNA-binding protein 33 ( Figure S22).…”
Section: Functional Analysis Of Potential Novel Lncrnas Involved In Cmentioning
confidence: 86%
“…Moreover, as noted above, TEs are the main target of epigenetic silencing, and therefore, the insertion of a TE within or close to a gene may bring the silencing machinery to this gene altering its expression ( Zhang H. et al, 2018 ). In addition to bringing new promoters and promoter elements, TEs can also be the source of small RNAs that regulate gene expression ( McCue and Slotkin, 2012 ), and in particular that of defense-related genes ( Poretti et al, 2020 ), and it has been recently shown that they can also contribute long non-coding RNAs that regulate plant stress responses ( Lv et al, 2019 ). TEs are therefore an important force that facilitates plant, and also animal ( Rech et al, 2019 ) and yeast ( Esnault et al, 2019 ), adaptation to stress.…”
Section: Combinatorial Genomic and Expression-level Responsesmentioning
confidence: 99%
“…The second is that lncRNAs tend to be expressed at lower levels than protein-coding genes, but with precise spatio-temporal patterns [55,56]. Thirdly, some lncRNAs contain parts of an exon, while a proportion of lncRNAs are derived from transposable elements (TEs) or contain remnants of TEs [57,58]. Here, we focus on the advance and regulatory function in plants responding to fungi underlying these properties and recent research on lncRNAs.…”
Section: Lncrnas In Plant Defense Against Fungal Stressmentioning
confidence: 99%
“…However, 1077 DE-lncRNA were predicted in maize during abiotic stress, like heat, cold, salt, and drought. Studies inferring co-expression networks revealed that 39 lncRNAs are major hubs in the co-expression networks, and 18 lncRNAs were considered to be derived from long-terminal-repeat transposable elements (TEs) [57]. A ceRNA network was constructed with the identified DElncRNAs, DEmiRNAs, and DEmRNAs in the roots of Ziyang Xiangcheng (Citrus junos) under Cu toxicity [97].…”
Section: Molecular Network Of Plant Lncrnas Related To Resistancementioning
confidence: 99%